Art as Radical Act: Teenagers Revisit Identity, Diversity, and Social Justice Through Contemporary Art. (3rd April 2022) - Song, Borim
Abstract : In this article, I share ways in which I have used the artworks of contemporary artists to encourage middle school students to reflect on the concepts of identity, diversity, and social justice. Specifically, I focus on the Comfort Hair series by Yuni Kim Lang, a Michigan-based Korean American artist, and a piece from the Giant series, "Kikito (Tecate, Mexico-USA, 2017), " by French street artist JR. When I shared images of the artworks with the students, the participating teenagers discussed the pieces verbally as well as textually via social media. They then created artworks based on their reflections. Although the quality of student outcomes varied in both the text-based discussions and drawing activity, they clearly showed that the work of Yuni Kim Lang and JR deeply engaged the students in a critical examination of the issues of identity and diversity and sparked their interest in the role of the visual arts as sources of social justice and systematical change.